Peculiarities of moral imperative influence upon legal institutions: socio-philosophical aspect - Харченко, С. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2017)
The article deals with socio-philosophical analysis of the influence of the moral imperative on the legal institutions.